Glycoluril dimer isomerization under aqueous acidic conditions related to cucurbituril formation - Stancl, Marek; Gargulakova, Zuzana; Sindelar, Vladimir (The Journal of organic chemistry, 2012)
A water-soluble methylene-bridged glycoluril dimer 2S was isolated. It was shown that 2S is the only kinetic product of the reaction between glycoluril derivative 1 and paraformaldehyde. Compound 2S is subsequently intermolecularly transformed into its diastereomer 2C. The kinetics and thermodynamics of the S- to C-shaped dimer isomerization were investigated under reaction conditions similar to those for cucurbituril synthesis.